The clinical implication of psychiatric illnesses in patients with alcoholic liver disease: an analysis of US hospitals. (3rd July 2022) - Lee, David Uihwan; Chou, Harrison; Wang, Edwin; Fan, Gregory Hongyuan; Han, John; Chang, Kevin; Kwon, Jean; Lee, Ki Jung; Blanchard, Jeremy; Urrunaga, Nathalie Helen
ABSTRACT: Background: In this study, we evaluate the clinical impact of psychiatric illnesses (PI) on the hospital outcomes of patients admitted with alcoholic liver disease (ALD). Methods: From the National Inpatient Sample from 2012–2017, patients with alcoholic cirrhosis or alcoholic hepatitis were selected and stratified using the presence/absence of PI (which was a composite of psychiatric conditions). The cases were propensity score-matched to PI-absent controls and were compared to the following endpoints: mortality, death due to suicide, length of stay (LOS), hospitalization charges, and hepatic complications. Results: After matching, there were 122, 907 PI with and 122, 907 without PI. Those with PI were younger (51.8 vs. 51.9 years p = 0.02) and more likely to be female (39.2 vs. 38.7% p = 0.01); however, there was no difference in race. Patients with PI had lower rates of alcoholic cirrhosis but higher rates of alcoholic hepatitis/alcoholic hepatic steatosis. In multivariate, patients with PI had lower rates of all-cause mortality (aOR 0.51 95%CI 0.49–0.54); however, they experienced higher rates of deaths due to suicide (aOR 3.00 95%CI 1.56–5.78) and had longer LOS (aOR 1.02 95%CI 1.01–1.02). Conclusion: Presence of PI in ALD patients is associated with prolonged hospital stay and higher rates deaths due to suicide.